1991
DOI: 10.1620/tjem.164.37
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation on Synthetic Precursors of Hydroxyapatite.

Abstract: The aim of this study was to investigate the reaction of skeletal tissue to various synthetic calcium phosphate (Ca-P) compounds in vivo. Five synthetic Ca-P compounds were implanted into the subperiosteal area of the calvaria of 7-week-old BALB/c mice for one to 15 weeks. Synthetic compounds were dicalcium phosphate (DCP), octacalcium phosphate (OCP), amorphous calcium phosphate (ACP), Ca-deficient hydroxyapatile and hydroxyapatile (HA). Implanted DCP, OCP and ACP were found to be converted to apatitic phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
342
1
8

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 261 publications
(364 citation statements)
references
References 35 publications
13
342
1
8
Order By: Relevance
“…The previous studies reported that periosteum contains osteoprogenitor cells that differentiate to osteoblasts in bone growth or fracturehealing (Iwasaki et al, 1995;Nakase et al, 1994). In our previous investigation, the subperiosteal implantation of octacalcium phosphate (OCP) enhanced new bone formation on the parietal bone surface (Sasano et al, 1995;Suzuki et al, 1991). Another set of our experiments using the membrane filter indicated that contact of periosteal cells with the bone surface may play a role in the new bone formation (Sasano et al, 1999), which has suggested the hypothesis that the osteoblastic differentiation of periosteum-derived progenitors is promoted by the contact with the bone matrix.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The previous studies reported that periosteum contains osteoprogenitor cells that differentiate to osteoblasts in bone growth or fracturehealing (Iwasaki et al, 1995;Nakase et al, 1994). In our previous investigation, the subperiosteal implantation of octacalcium phosphate (OCP) enhanced new bone formation on the parietal bone surface (Sasano et al, 1995;Suzuki et al, 1991). Another set of our experiments using the membrane filter indicated that contact of periosteal cells with the bone surface may play a role in the new bone formation (Sasano et al, 1999), which has suggested the hypothesis that the osteoblastic differentiation of periosteum-derived progenitors is promoted by the contact with the bone matrix.…”
Section: Discussionmentioning
confidence: 97%
“…The previous studies indicated that when blocks composed of hydroxyapatite, tricalcium phosphate or octacalcium phosphate are implanted on the bone surface, new bone formation occurs from the adjacent bone surface to the surface of the block and eventually the implanted block is surrounded by new bone (Chang et al, 1996;Cornell and Lane, 1998;Hotz and Herr, 1994;Kamakura et al, 1996;Sasano et al, 1995Sasano et al, , 1999Suzuki et al, 1991). Our previous studies demonstrated that the octacalcium phosphate (OCP) causes new appositional bone formation on it when implanted in the subperiosteal region of murine bone (Kamakura et al, 1996;Sasano et al, 1995;Suzuki et al, 1993), whereas no bone formation is identified on the OCP when the implant is placed on the membrane filter under the periosteum to prevent the periosteum from contacting the bone surface (Sasano et al, 1999).…”
mentioning
confidence: 99%
“…The FTIR spectrum of the calcium phosphate precipitate, obtained through the preparation condition which was the same with the coating, was obtained by FTIR spectroscopy (FREEXACT-2; HORIBA, Kyoto, Japan), with the sample diluted with KBr over a range of 4,000-400 cm -1 with 4 cm -1 resolution, and compared with HA. The HA used as control material is a synthetic non-sintered HA and well characterized as reported previously, having a stoichiometric Ca/P molar ratio 1.67 of HA 13) .…”
Section: Characterization Of Cap Coatingmentioning
confidence: 99%
“…Existen en la literatura gran cantidad de artículos en los que se pone de manifiesto que tanto la HA como otras sales de fosfato cálcico se reabsorben y son sustituidas gradualmente por tejido óseo 10,12,38,41 . Con objeto de evaluar la evolución en el tiempo del cemento usado en nuestro caso, comparamos retrospectivamente los exámenes realizados al paciente con fechas 16 En el examen inicial (figura 1) se observan los dos aportes de cemento desde los pedículos y una fuga de material que llega al espacio epidural siguiendo el agujero nutricio vertebral.…”
Section: Discussionunclassified
“…Todos los estudios que hemos encontrado en la literatura 10,12,38,41 tratan sobre la evolución del material de refuerzo dentro de un ambiente óseo, pero no hacen referencia a cómo evolucionaría el mismo fuera del espacio vertebral. Dado que la fuga de cemento mantiene continuidad con el interior de la vértebra, cabría pensar que podría producirse una osificación de la misma que progresase desde el punto de fuga hacia el exterior o bien el cemento extravasado podría provocar una osificación ectópica aun cuando perdiese contacto con el interior vertebral, aunque nosotros no hemos observado estos comportamientos.…”
Section: Discussionunclassified